2023
DOI: 10.2196/47902
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cause-Specific Injury Mortality in China in 2005-2019: Longitudinal Observational Study

Abstract: Background Over the last few decades, although the age-standardized mortality rate (ASMR) of injury has shown a significant declining trend in China, this pattern has dramatically reversed recently. Objective We aimed to elucidate the geographical, demographic, and temporal trends of cause-specific injuries, the reversal phenomenon of these trends, and the fluctuations of injury burden from 2005 to 2019 in China. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“… 83 Although suicide among adolescents has been increasing over the long term, most studies from other OECD countries have reported that adolescent CSMRs decreased or remained unchanged during the pandemic. 84 , 85 , 86 , 87 , 88 In contrast, in Japan, CSMRs of males and females of 10–19 years began to increase before the pandemic. 12 , 25 , 26 , 28 To date, there have been no causality analyses using independent variables that may affect the specific temporal fluctuations of adolescent CSMRs.…”
Section: Causality Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“… 83 Although suicide among adolescents has been increasing over the long term, most studies from other OECD countries have reported that adolescent CSMRs decreased or remained unchanged during the pandemic. 84 , 85 , 86 , 87 , 88 In contrast, in Japan, CSMRs of males and females of 10–19 years began to increase before the pandemic. 12 , 25 , 26 , 28 To date, there have been no causality analyses using independent variables that may affect the specific temporal fluctuations of adolescent CSMRs.…”
Section: Causality Analysesmentioning
confidence: 97%
“…Adolescence is a period of psychosocial and biological development that involves various social statuses (e.g., middle school, high school, university, and special vocational school students and working young adults) 83 . Although suicide among adolescents has been increasing over the long term, most studies from other OECD countries have reported that adolescent CSMRs decreased or remained unchanged during the pandemic 84–88 . In contrast, in Japan, CSMRs of males and females of 10–19 years began to increase before the pandemic 12,25,26,28 .…”
Section: Causality Analysesmentioning
confidence: 99%
“…Between 2009 and 2021, suicide was the leading cause of death among adolescents in Japan [59,60]. Although suicide rates among adolescents have globally been increasing over time, most studies from other OECD countries have reported that adolescent SMRs decreased or remained unchanged during the pandemic [61][62][63][64][65], whereas in Japan, it has been reported that the SMRs of both males and females under 20 years old increased during the pandemic [39][40][41]66,67]. These reports attributed the increase in adolescent SMRs to major lifestyle changes during the pandemic, particularly pertaining to the impaired ability to engage in recreational and educational opportunities and being forced to spend much of their time at home due to social restriction measures [39][40][41]66,67].…”
Section: Suicides Among Adolescents and The Elderlymentioning
confidence: 99%
“…It is commonly perceived that higher disease burdens are often directly associated with worse socio-economic status and fewer healthcare resources [ 14 16 ]. However, as a consequence of socio-economic progress, burdens of some disorders, such as falls among the elderly, mental health issues among youngsters, and neurological disorders, have tended to grow recently [ 5 , 17 , 18 ], which seem to conflict with health and well-being within the context of sociodemographic and economic development. Among these, mental illnesses, Alzheimer’s disease, and Parkinson’s disease, etc., are more directly associated with societal changes, which seem to stem from the growth of an aging population [ 10 ], rising social stress [ 19 , 20 ], deteriorating sleep issues [ 21 ], and illogical eating habits [ 22 ].…”
Section: Introductionmentioning
confidence: 99%